The Impact of Health Legal Policy on the Accessibility of Eyewear in Health Insurance (Architecture Image Studies, 2025)
This study examines the effectiveness of national health law policies in ensuring accessibility to eyeglasses through health insurance mechanisms and identifies the legal, administrative, and social barriers faced by insurance participants in obtaining reimbursement rights. The purpose of this study is to assess the extent to which national health law policies are able to meet public access to eyeglasses and formulate solutions to existing obstacles. The research method used is normative legal research with legislative, conceptual, and case approaches, and processing secondary data in the form of regulations, scientific literature, and related court decisions. The results show that although national regulations provide a fairly strong legal framework, their implementation still faces significant obstacles in the distribution of facilities, complicated claims procedures, limited subsidy values, and low literacy among insurance participants. Sociocultural and economic factors also influence the utilization of the right to reimbursement rights for eyeglasses. Proposed solutions include harmonizing national regulations with international human rights norms, simplifying administrative procedures through digitalization, and increasing public education and outreach. In conclusion, health law policies must be strengthened and optimized to ensure fair and equitable access to eyeglasses through the national health insurance system.